2016
DOI: 10.1128/jvi.01409-16
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Immunogens Targeting HIV-1 gp120 V1V2 Induce Distinct Conformation-Specific Antibody Responses in Rabbits

Abstract: The V1V2 region of HIV-1 gp120 harbors a major vulnerable site targeted by a group of broadly neutralizing monoclonal antibodies (MAbs) such as PG9 through strand-strand recognition. However, this epitope region is structurally polymorphic as it can also form a helical conformation recognized by RV144 vaccine-induced MAb CH58. This structural polymorphism is a potential mechanism for masking the V1V2 vulnerable site. Designing immunogens that can induce conformation-specific antibody (Ab) responses may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 57 publications
(71 reference statements)
1
68
0
Order By: Relevance
“…The immunogenic properties of the V2 region were also shown by the isolation of glycan-dependent V2-targeting bNAbs from chronic infected individuals (McLellan et al, 2011; Walker et al, 2009) and isolation of monoclonal antibodies with ADCC activity from RV144 clinical trial vaccine recipients (CH58-59) (Liao et al, 2013), encouraging the design of V2-based immunogens (Jiang et al, 2016; Mayr et al, 2013). Further, the V2 region was shown to interact with the integrin α4β7 (Arthos et al, 2008) proximal to the region where the vaccine-induced mAbs reported here bind.…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenic properties of the V2 region were also shown by the isolation of glycan-dependent V2-targeting bNAbs from chronic infected individuals (McLellan et al, 2011; Walker et al, 2009) and isolation of monoclonal antibodies with ADCC activity from RV144 clinical trial vaccine recipients (CH58-59) (Liao et al, 2013), encouraging the design of V2-based immunogens (Jiang et al, 2016; Mayr et al, 2013). Further, the V2 region was shown to interact with the integrin α4β7 (Arthos et al, 2008) proximal to the region where the vaccine-induced mAbs reported here bind.…”
Section: Discussionmentioning
confidence: 99%
“…V1V2 is presented by the 2F5K and 2J9C scaffolds as an apical trimeric structure whose conformation is constrained by their insertion in these scaffolds (47). In contrast, the V1V2 region in gp120 is presented as a monomeric, unconstrained domain.…”
Section: Discussionmentioning
confidence: 99%
“…Genes of the V1V2 scaffolds were chemically synthesized and cloned into the pVRC8400 plasmid, followed by expression in HEK293 GnTI Ϫ/Ϫ cells and purification by affinity chromatography (46). Details of the design and construction of the immunogens are described separately (47). The V1V2-tags protein of strain 1086 (V1V2 1086 -tags) and V1V2 A244 -tags were provided by H. Liao (Duke University), V1V2 CaseA2 -gp70 and V1V2 92TH023 -gp70 were provided by A Pinter, and gp120 A244 was provided by Global Solutions for Infectious Diseases (South San Francisco, CA).…”
Section: Methodsmentioning
confidence: 99%
“…2). Structures of apex V1V2-directed antibodies (PG9, PG16 [41,42] and more recently CH03 [44••]) in complex with V1V2 domain-scaffolds have been used as templates for glycosylated V1V2 peptide [111] and V1V2-epitope scaffold immunogens [112,113•]. Structures of N332 glycan patch directed antibodies (PGT128, PGT135, PGT122 [51,53,54]) with gp120 core or HIV-1 Env trimer have highlighted a supersite of vulnerability that can be targeted from different angles and have led to designs of V3 glycosylated peptides [115•] and V3 epitope scaffolds [112].…”
Section: Vaccine Design Incorporating Bnab Insights and Env Conformationmentioning
confidence: 99%